(untitled) (Journal of Parents and Teachers, 1996)
The article explores the importance of the gaze and how it can convey deep emotions and intentions. It is mentioned that the gaze not only reflects the perception of the other but can also be a tool for intimate connection and desire. In addition, the cultural and psychological implications of the gaze in human relationships are discussed.